Rhetorical use of displayed emotions in resource mobilization: A proposal of a pedagogy - Valor Martínez, Carmen (My University, 2025)
Despite the importance of displayed emotions in mobilizing resources for nascent ventures, entrepreneurship education has overlooked nurturing interpersonal emotional skills. To address this gap, this study first reviews the literature to explain how and why entrepreneurs' emotional displays persuade investors. A systematic review of 61 articles –which together reported 85 empirical studies-examining emotional displays that are more persuasive for investors is integrated into a comprehensive model based on social-functionalist theories of emotions. The model reveals that emotional displays impact entrepreneurial funding in the following complex ways: (1) different emotional displays can lead investors to similar inferences shaped by perceived authenticity, credibility, and appropriateness; (2) emotions can be conveyed through various means, with nonverbal emotional displays proving more persuasive than verbal displays; and (3) the same emotional display differently influences professional and nonprofessional investors. Building on these findings, we then present a pedagogy for developing interpersonal emotional skills among entrepreneurs. The proposed pedagogy outlines what to teach, grounded in the aforementioned model; how to teach, which draws on dramatic arts and emotional regulation theory; and how to identify instructors and target audiences. This approach benefits entrepreneurship training centers and students while also serving as a self-training resource for current entrepreneurs. This article presents the first comprehensive synthesis of emotional displays’ persuasiveness in funding interactions, addressing the need for further exploration of interpersonal emotional dynamics in entrepreneurship. It also contributes to entrepreneurship education scholarship by proposing a pedagogy model that instructors and entrepreneurs can use to develop skills in using expressed emotions as persuasive tools.
Artículos en revistas
Keywords: Instituto de Investigación Tecnológica (IIT) - Empresa, economía y sostenibilidad (E-SOST)